Dialektika Hukum dan Identitas dalam Perubahan Nama di Pengadilan Negeri Gorontalo - Nijam Hiliwilo; Fence M. Wantu; Mohamad Hidayat Muhtar (Suara Edukasi Hukum, 2025)
This research discusses Decision Number 67/Pdt.P/2024/PN Gto at the Gorontalo District Court regarding a request to change a child's name from "Nadelia Nazwa Putri Baune" to "Aurel Syahwana Putri Baune," filed by the parents for administrative convenience. The study focuses on analyzing the judges' legal considerations in granting the application, emphasizing the relationship between compliance with formal norms, the relevance of the reasons presented, and the social sensitivity inherent in the case. Data was collected thru a study of judgment documents, interviews with judges, and analysis of relevant legal literature. The research results show that judges use a combination of legal-formal considerations based on the Population Administration Law and the principle of expediency, which emphasizes the smooth administration of children. Although the applicant's reasons were considered simple, the judge still deemed the application valid because it did not contradict the law, did not harm third parties, and was supported by administrative evidence and witnesses. However, critical analysis shows that the judges' ratio decidendi tends to be more pragmatic than in-depth, potentially setting a permissive precedent in similar cases. In conclusion, this decision reflects legal practices that are responsive to societal needs, but it still requires strengthening legal argumentation standards to balance legal certainty, justice, and utility.